2005
DOI: 10.1111/j.1572-0241.2005.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Esomeprazole on Nighttime Heartburn and Sleep Quality in Patients with GERD: A Randomized, Placebo-Controlled Trial

Abstract: Esomeprazole reduced nighttime heartburn and GERD-related sleep disturbances and improved sleep quality and work productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
151
1
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 17 publications
8
151
1
12
Order By: Relevance
“…The PSQI was used to evaluate the sleep quality during the month preceding the study and is widely used in other surveys too. [22,23] Our results were consistent with Rutenfranz et al, [24] who reported that, almost 70% of night shift workers complained of sleep disorders, assessing their sleep as unsatisfactory, insufficient, and little restorative.…”
Section: Sleep Qualitysupporting
confidence: 82%
“…The PSQI was used to evaluate the sleep quality during the month preceding the study and is widely used in other surveys too. [22,23] Our results were consistent with Rutenfranz et al, [24] who reported that, almost 70% of night shift workers complained of sleep disorders, assessing their sleep as unsatisfactory, insufficient, and little restorative.…”
Section: Sleep Qualitysupporting
confidence: 82%
“…34 Several studies have also shown that the response rate of PPI once daily for nighttime heartburn is significantly lower (up to 53%) than the response rate for daytime heartburn (up to 66%). 35,36 In summary, nighttime heartburn has the most important impact on the quality of life for GERD patients. However, night-time heartburn appears to be less responsive to antireflux treatment than daytime heartburn.…”
Section: Nighttime Heartburnmentioning
confidence: 99%
“…12 Considerably higher levels of reduced work productivity have been observed in untreated patients with troublesome GERD symptoms [13][14][15][16] ; in those with GERD-related sleep disturbance, for example, the mean reduction in productivity was up to 40%. 16 PPI therapy to resolve GERD symptoms helps to address this burden and improves work productivity.…”
mentioning
confidence: 99%
“…12 Considerably higher levels of reduced work productivity have been observed in untreated patients with troublesome GERD symptoms [13][14][15][16] ; in those with GERD-related sleep disturbance, for example, the mean reduction in productivity was up to 40%. 16 PPI therapy to resolve GERD symptoms helps to address this burden and improves work productivity. 15,16 Further, a casecontrol study using objective measurements of hourly and annual at-work productivity confirms that GERD, indeed, has a significant impact on productivity while at work, 17 which supports validity of patient-reported productivity assessments.…”
mentioning
confidence: 99%
See 1 more Smart Citation